Factors influencing family takaful ownership among B40 segment in Kelantan - Nur Fatihah Azman; Nurul Farah Ain Mohamad; Siti Nor Farisya Ahmad Fodzi (2022)
In a tougher economic climate, the family takaful or life insurance contributes significantly to economic security for individuals, particularly the bottom 40% of income households (B40), who can be categorized as vulnerable groups to economic shocks. However, Takaful or insurance coverage ownership remains extremely low among the B40, at only 4%. There are several major factors that contribute to the low level of family takaful penetration among B40. Thus, the purpose of this study is to determine the factors influencing family takaful ownership among B40 in Kelantan. The data for this study were gathered by quantitative method which a set of questionnaires distributed evenly among 384 respondents via Google Form. The Statistical Package for Social Science (SPSS) was used to analyses the data. According to the survey, the findings show the family takaful ownership among B40 is positively correlated with levels of awareness, social influence, and financial capability. The implication of this study is the government intervention especially Bank Negara Malaysia (BNM), and insurance or takaful companies must collaborate to provide consumer-friendly products that benefit B40 households. The goal of the collaboration is to customise products based on their features and constraints. Among them are providing various packages that focus on them.